P.002 Neurodevelopment at 2 years in asphyxiated newborns treated with hypothermia can be predicted by early neuroimaging markers. (17th June 2016) - Al Amrani, FJ; Wintermark, P
Abstract : Background: Brain imaging in asphyxiated newborns treated with hypothermia has shown that brain injury can be identified as early as day 2 of life and continue to evolve over the first month of life. Methods: Asphyxiated newborns treated with hypothermia were enrolled prospectively. Apparent diffusion coefficient (ADC) and fractional anisotropy (FA) were measured on magnetic resonance imaging (MRI) performed over the first month of life. Neurodevelopment was evaluated around 2 years of age. Results: Twenty-six asphyxiated newborns treated with hypothermia were enrolled. In asphyxiated newborns treated with hypothermia, who developed cerebral palsy, ADC values were significantly decreased on day 1 of life, on day 2-3 and around day 10 of life in the thalamus. In the same newborns, the FA values were significantly decreased on day 10 of life. Conclusions: Early MRI measurements permitted to identify the newborns developing cerebral palsy as early as on day 1 of life and could thus be used in the future to predict the long-term neurodevelopmental outcome asphyxiated newborns treated with hypothermia.